Pengaruh Budaya Perusahaan Terhadap Kinerja Dan Kreativitas Karyawan Pada PT Surya Nusantara Sentosa - Febriyano Ade Ilham; Dania Oktaviani; Mohamad Zein Saleh (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to understand the impact of organizational culture on the performance and creativity of staff at PT Surya Nusantara Sentosa (SNS.AC), a vehicle air conditioner repair service company located in Bintaro. Organizational culture is considered a crucial element in shaping behavior, motivation, and innovation within teams. The methodology used is a descriptive qualitative approach, with data collected through observation and interviews. The findings of this study indicate that a positive and supportive organizational culture has a significant impact on improving employee performance and creativity. Conversely, a negative or unsupportive culture can reduce work enthusiasm, innovation, and employee loyalty. Therefore, the strategic management of organizational culture is essential to achieving the overall goals of the company.